Resiliência e vulnerabilidade ao estresse no trabalho em policiais civis de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The police profession is considered highly stressful for many researchers, due to working conditions characterized by adversity in relation to safety and the risk of life, emphasizing that stress is also related to individual issues and not only the environment. In order to investigate the level of vulnerability to stress perceived by these professionals and correlations with levels of resilience, a survey was conducted quantitative cross. Participants were 131 civilian police in Manaus, including delegates, clerks, investigators and experts, with an average of 35 years of age, mostly male and married. The instruments used were: Sociodemographic Questionnaire, Vulnerability Scale to Work Stress (EVENT) and Resilience Scale for Adults (RSA). The results showed higher mean score on all factors of the instrument EVENT, with a greater representation in the factor Infrastructure and routine. The Resilience Scale for Adults showed high score, and the factor more representative was Social Resources and the less representative was the Structured Style. In this study there was no significant correlation between resilience and vulnerability to stress from work. As for the influence of sociodemographic factors on stress and resilience, there was a significant difference only regarding sex for the stress, these findings indicate that male police officers had levels of vulnerability to job stress higher than female police officers.
Keywords: Policiais civis; Estresse; Resiliência; Police civilian; Stress and resilience; CIÊNCIAS HUMANAS: PSICOLOGIA